EXPLORING ENVIRONMENTAL DEGRADATION IN YOLA SOUTH LOCAL GOVERNMENT AREA, ADAMAWA STATE - Adamu, Ibrahim M; Abubakar , Fatima N (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
This paper aimed to overview environmental degradation in Yola South Local Government Area, Adamawa State. The present paper summarizes pertinent information on environmental degradation in the area through investigating limited available and pertinent studies conducted in the area coupled with field observations and interviews which form the basis of the secondary data for the research. It was identified that drought, flood, soil degradation/erosion and deforestation were the major types of environmental degradation. Similarly, it was also revealed human factor is the most inducing of creating such menace than the natural factor. Loss of properties, lives, destruction of farmlands and buildings, paralysis of socio-economic activities and ecosystems deterioration were among the generated effects caused by the processes of environmental degradation in the area. It is therefore, suggested that government should ensure effective monitoring of the environmental resources and protecting them through formulating and adoption of polices and strategies that will not only safeguard the resources but will also improve and sustain them for future growth and development in the study area